Is Regular Physical Activity Practice During a Submarine Patrol an Efficient Coping Strategy? - Martin-Krumm, Charles; Lefranc, Barbara; Moelo, Alan; Poupon, Charlotte; Pontis, Julien; Vannier, Alexandre; Trousselard, Marion (Frontiers in Psychiatry, 2021)
Introduction: A nuclear-powered ballistic missile submarine (SSBN) is a singular professional environment, exposing personnel to isolation and confinement amidst sophisticated technology for the duration of a mission. Submariners see their mood and cognition deteriorate as their mission progresses. With regard to the benefits of physical activity (PA) on mental health, this study evaluates the impact of regular PA on the maintenance of thymia and sensory functioning during patrols. Method: This pragmatic exploratory cohort follow-up study included 29 volunteer submariners before, during and 1 month after return from patrol. PA practice was evaluated by a daily self-questionnaire. This allowed submariners to be classified into two groups according to the median of the total duration in minutes of a sport practiced during the patrol (PA practicing submariners and non-practicing). Changes in mood and psychological activation, health (including sleep), unipodal stability and accommodation distances were compared between the two groups over the period of the patrol. Results: Overall thymic functioning deteriorated during the patrol. Submariners who practice PA maintain a stable level of activation unlike non-practicing PA submariners, but they exhibited both worse general health and sleep at recovery. For these personnel, postural control is better at the end of the patrol and far visual accommodation tends to be preserved. Conclusion: PA during patrol alone is not sufficient to compensate for the thymic dysregulation induced by the SSBN environment. Nevertheless, it seems to help in maintaining an exteroceptive functioning. This exploratory study suggests directions for possible future research on physical activity associated with sensory stimulation amongst submariners, and more generally amongst people working in isolated and confined environments.